حقوق المكلف بالضريبة كضمانة للحد من سلطات الإدارة الجبائية في الجزائر - علالى, محسن; قمولة, عبد الجبار (جامعة الوادي university el-oued, 2021)
إنه من الضروري القول بأن للضریبة دورا هاما في التنمية الإقتصادية بإعتبارها المورد الأساسي للخزینة العمومية, ما جعل المشرع يحرص على إيجاد منظومة قانونية تعمل في الوقت ذاته على دعم أسس العدالة الضریبیة المنصوص علیها دستوریا, و ضمان حقوق المكلفين بالضريبة . ولذلك تناولنا هذا الموضوع إنطلاقا من عرض الحقوق التي يتمتع بها المكلفين بالضريبة, بوصفها ضمانات تحد من السلطات الواسعة الممنوحة للإدارة الجبائية والتي قمنا بشرحها هي الأخرى. مع تبيان مسعى المشرع في إيجاد توازن بين طرفي العلاقة الضريبية من خلال مختلف التعديلات التي وردت بموجب قوانين المالية والتي تهدف إلى حماية المكلفين . وهو ما قادنا إلى تبيان الأطر الخاصة بالمنازعة التي يمكن للمكلفين بالضريبة اللجوء إليها, في مراحلها الإدارية من خلال الشكاوى أو التظلم أمام اللجان. أوفي مراحلها القضائية من خلال رقابة القاضي الإداري لكون المنازعة الجبائية تدخل ضمن إختصاصاته. Il est toujours utile de dire que l'impôt a un rôle important dans le développement économique car c'est la principale ressource du trésor public, ce qui a poussé le législateur à chercher de mettre en place un système juridique, qui prévoie le soutien des fondements de la justice fiscale prévue par la constitution et au temps même de garantir les droits des contribuables. C'est pourquoi nous avons traité ce sujet à partir de la présentation des droits prévue pour les contribuables, comme des garanties limitant les larges pouvoirs accordés à l'administration fiscale, que nous avons également expliqués. En montrant la volonté du législateur de trouver un équilibre entre les deux parties à la relation fiscale à travers les différentes modifications apportées aux lois de finances, qui visent à protéger les contribuables Ce qui nous a conduits à préciser les cadres régissant les litiges fiscaux, auxquels les contribuables peuvent recourir, dans leurs étapes administratives, par le biais de requête ou de griefs devant les commissions. Dans ses étapes judiciaires, par le biais du contrôle du juge administratif, comme le litige fiscal relève de sa compétence.It is always useful to say that the tax has an important role in economic development as it is the main resource of the public treasury, which has prompted the legislator to seek to put in place a legal system, which provides for the support of foundations of tax justice provided for by the constitution and at the same time to guarantee the rights of taxpayers. This is why we have treated this subject from the presentation of the rights provided for taxpayers, as guarantees limiting the broad powers granted to the tax administration, which we have also explained. By showing the legislator's desire to find a balance between the two parties to the fiscal relationship through the various changes made to finance laws, which aim to protect taxpayers This has led us to specify the frameworks governing tax disputes, to which taxpayers can resort, in their administrative stages, by means of petitions or grievances before the commissions. In its judicial stages, through the control of the administrative judge, as the tax dispute falls within its competence.It is always useful to say that the tax has an important role in economic development as it is the main resource of the public treasury, which has prompted the legislator to seek to put in place a legal system, which provides for the support of foundations of tax justice provided for by the constitution and at the same time to guarantee the rights of taxpayers. This is why we have treated this subject from the presentation of the rights provided for taxpayers, as guarantees limiting the broad powers granted to the tax administration, which we have also explained. By showing the legislator's desire to find a balance between the two parties to the fiscal relationship through the various changes made to finance laws, which aim to protect taxpayers This has led us to specify the frameworks governing tax disputes, to which taxpayers can resort, in their administrative stages, by means of petitions or grievances before the commissions. In its judicial stages, through the control of the administrative judge, as the tax dispute falls within its competence.
مذكرة ماستر
Keywords: : حقوق المكلفين بالضریبة، سلطات الإدارة الجبائية، الحمایة القانونیة للمكلفين بالضریبة، المنازعة الضریبة; droits des contribuables, les autorités de l'administration fiscale, protection juridique des contribuables, contentieux fiscal.; rights of taxpayers, tax administration authorities, legal protection of taxpayers, tax litigation.